Heterogeneous and homogeneous EC and ECE processes at channel electrodes: Analytical wave shape theory - Morland, P; Compton, R (1999)
Analytical theory is developed for EC and ECE processes, both homogeneous and heterogeneous, occurring at channel electrodes for the case where the electron transfer is electrochemically reversible. In particular the variation of the half-wave potential with solution flow rate and/or cell geometry is shown to provide a sensitive indication of electrode reaction mechanism type. Simple expressions are presented which allow the ready mechanistic interpretation of experimental data and the deduction of corresponding rate constants.